Kendala-Kendala Realisasi Pendirian Badan Usaha Milik Nagari (BUMNag) : Studi di Nagari Padang Tarok Kecamatan Baso Kabupaten Agam - M.Hidayatul Halim (Jurnal Sosiologi Andalas, 2020)
Abstract : One of the priority programs mandated by Law No. 6/2014 on traditional villages or villages in Indonesia is the establishment of BUMDes. BUMDes or for West Sumatra Province is called BUMNag, is a business entity formed by the village government which aims to improve the economy in the village and can take advantage of the potential that exists in the village, so as to improve the welfare of the people in the village. However, not all villages have been able to establish BUMNag, one of which is Nagari Padang Tarok. Therefore, researchers want to see what are the obstacles faced by Nagari Padang Tarok, so that BUMNag has not yet been established. This research was conducted with a qualitative approach with a descriptive type. Research informants were selected using purposive sampling technique and in data collection used in-depth interviews. The results of this study found the obstacles faced by the Padang Tarok Nagari Government in establishing BUMNag, namely that the village government prioritized physical development, difficulty finding business units and lack of human resources. The focus of the village government in physical development in Nagari Padang Tarok has a positive impact on the community, road access is getting better between jorong and another, irrigation in the fields is starting to run smoothly, health and education facilities are starting to be adequate.